A reterospective study of maternal and fetal outcome of adolescent pregnancy in Kawthaung province, Myanmar - Aung, Soe Htet (Bangladesh Journal of Medical Science, 2017)
Objectives : To study maternal and neonatal outcomes of adolescent pregnancies (< 19 years) and to compare the outcomes with pregnant women between 20-34 years. Materials and Methods: This retrospective comparative study was performed in No. (13), Military Hospital (100) Bedded from 1stNovember 2014 to 31st October 2015. The case records of all adolescent mothers who delivered in hospital were retrieved. The major complications and the outcome were compared between adolescent mothers and adults mothers (20 -34 years) who delivered in the same period. Results: During the study period there were 262 deliveries in our hospital, of which 64 (24.4%) were teenage mothers. The mean age of the adolescent mothers was 18.01 (±0.95) and mean gestational period of adolescent mothers was 37.8 weeks (±1.23), comparing to mean age of adult pregnancy was 27.45 (±3.8) and the gestational period was 38.7 weeks (±0.95), Adolescent mothers were significantly higher in inadequate AN visits (18.3% vs. 11.4%), Serology Positive at AN visit (16.7 % vs. 6.4 %), anemia (23% vs. 7.8%), PROM (26.7% vs. 15.1%), eclampsia (15% vs. 6.6%), emergency CS (31.7% vs. 18.7%), poor Apgar score (10% vs. 3 %) and low birth babies (11.6% vs. 3%). Conclusions: Pregnant teenagers are definitely at greater risk, requiring more attention and effective antenatal care for prevention and treatment of anemia, prematurity, IUGR and LBW. To prevent the adverse outcome, steps should be taken to avoid teenage pregnancies by creating public awareness and health education about reproductive health in Kawthaung province. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.535-540